Efecto del extracto etanólico de las hojas de Stevia rebaudiana (Bertoni) Bertoni sobre Escherichia coli - Meregildo Alayo, Heiner Anderson (2020)
The objective of this research work is to determine the effect of the ethanolic extract of the leaves of Stevia rebaudiana (Bertoni) Bertoni on Escherichia coli. Stevia rebaudiana leaves were provided by the San José experimental center, then washed with bleach, distilled water and dried at room temperature, then a fine powder was obtained, then 600g of the fine powder was weighed and diluted in 1800 ml of ethyl alcohol of 96º also taken to maceration for seven days and finally taken to a rotary evaporator until obtaining the extract. The design was completely randomized with nine treatments and four repetitions at concentrations of 5%, 10%, 15%, 20%, 25%, 50%, 75% of the ethanolic extract of Stevia rebaudiana leaves. The culture medium used was Müller Hinton. In addition, susceptibility, inhibition effect, analysis of variance and the Tukey test were determined to demonstrate significant differences between treatments. Concluding that the ethanolic extract of the Stevia rebaudiana leaves in the concentration of 75% had the greatest inhibitory effect of 66.25% on E. coli and the concentrations 5%, 10%, 15%, had an effect under effect. Likewise, the concentrations of 20%, 25%, 50% and 75% showed a limit sensitivity against E. coli.